ENVIRONMENT, WATER AND TERRITORY: DIAGNOSIS AND METHODOLOGICAL ANALYSIS OF WATER RESOURCES MANAGEMENT IN A WATERSHED OF HIGHLANDS OF JALISCO MEXICO - Villanueva, Aldo Antonio Castañeda; Pérez, Cándido González; Nuño, Raymundo Velasco (European Scientific Journal, ESJ, 2015)
For the management of natural resources, one option is integrated partial management of small watersheds; specifically the local management of water bodies as amalgam both bio-physical, socio-cultural elements, such as falling within the watershed itself. In the present work advances in the diagnosis and methodology of the research project on the quality and availability of water resources in the watershed of "Jihuite" and its interrelation with the growth of the city of Tepatitlán, Jalisco exposed, because of the change on land use, population growth and agricultural and industrial development of the region in the last 25 years. The watershed of the Jihuite is located 6 km from the city of Tepatitlán, belongs to the subbasin of the Rio Verde, the Santiago basin and the hydrologic region Lerma- Santiago-Pacific, with an area of approximately 60 km². By the methodological approach of Cultural Ecology and various quantitative and qualitative stages, such as parametric data collection on quality and degree of availability, statistical techniques (principal component analysis) and the use of participatory geographic information systems, as well as interviews, surveys and field trips local uses and handling of water bodies were addressed, by the different users of the watershed, identifying strengths and weaknesses of the current program for local water management, in order to promote local management alternatives that offer greater certainty and sustainability of the resource.